Regional Rights, Environmental Wrongs: Unpacking the Paradox of Autonomy in Indonesia's Environmental Governance - Sagita, Grandini Dyah; Budi, Ervira Rahmasari (Indonesian Journal of Environmental Law and Sustainable Development, 2024)
This paper delves into the complex interplay between regional autonomy and environmental governance in Indonesia, shedding light on the paradoxical outcomes that arise from decentralized decision-making. It examines how the delegation of power to local authorities has both empowered and challenged efforts to enforce environmental regulations and protect natural resources. Through a comprehensive analysis, the paper elucidates the ways in which regional autonomy has led to divergent approaches to environmental management across Indonesia's diverse regions. While some local governments have demonstrated commendable commitment to environmental conservation, others have prioritized economic interests at the expense of environmental sustainability, leading to widespread degradation and ecological harm. Drawing on case studies and empirical evidence, the paper unpacks the factors contributing to this paradox, including varying levels of institutional capacity, political dynamics, and socio-economic pressures. It highlights instances where regional autonomy has resulted in regulatory loopholes, weak enforcement mechanisms, and conflicts of interest, exacerbating environmental challenges and undermining national conservation efforts. Furthermore, the paper explores potential pathways for reconciling the tension between regional rights and environmental wrongs in Indonesia. It advocates for a holistic approach to environmental governance that integrates principles of subsidiarity with national environmental priorities, fostering collaboration between central and local authorities, and promoting community engagement and empowerment. In conclusion, the paper underscores the imperative of addressing the paradox of autonomy in Indonesia's environmental governance.